PHILOSOPHICAL QUESTIONS AND BIOLOGICAL FINDINGS, PART II: PLAY, ART, RITUAL, AND RITUAL SACRIFICE: with Marcia Pally, "Philosophical Questions and Biological Findings, Part I: Human Cooperativity, Competition, and Aggression" and Marcia Pally, "Philosophical Questions and Biological Findings, Part II: Play, Art, Ritual, and Ritual Sacrifice.". Issue 4 (26th September 2020) - Pally, Marcia
Abstract: This Part II of a two‐part article illustrates how research in evolutionary biology, anthropology, archeology, and psychology illuminates questions arising in philosophy—specifically questions about René Girard's theory of aggression. Part I looked at: (i) how old the systemic practice of severe aggression is; (ii) how much of it results from humanity's mimetic/social and competitive nature and how much from ecological, resource, and cultural conditions; and (iii) if ecological, resource, and cultural conditions are important, might we adapt this information toward greater cooperativity today? Part II investigates Girard's theory of ritual sacrifice—especially human sacrifice—as a societal steam valve for the systemic aggression explored in Part I. It draws on theories of play, theater, and art to examine the role and function of such ritual sacrifice.